ANALYSIS OF OCT-A PERFORMED AMONG NAION PATIENTS VERSUS OTHER CAUSES - Usamah Haidar; Riski Prihatningtias (Majalah Oftalmologi Indonesia, 2025)
Introduction: Non-Arteritic Anterior Ischemic Optic Neuropathy (NAION) is the type of optic neuropathy with crowding structural of microcirculation on optic nerve head. The vascular factor has the role on its pathophysiology. The aim of this study to analyse OCT-A among NAION patients compared to patients of papil atrophy with other causes. Methods: A retrospective case control study held from medical record of patients. Two group diagnosis of NAION and papil atrophy due to other causes who performed OCT-A in Dr. Kariadi Hospital Semarang. The analysis of the study including vessel perfusion density (VPD) and flux index (FI) among two groups. The bivariate analysis is using Independent-T test. Results: Totally 40 patients consisted of 20 NAION (12 bilateral eyes) and 20 papil atrophy with other causes (15 bilateral eyes). Age over 50 years old were 19 NAION (95%) and 17 other causes (85%). The results found there is statistically significant difference between VPD among NAION and other causes in average, superior, and nasal (p value <0.05, respectively 0.008, 0.008, 0.030), but there is no significant difference between FI among NAION and other causes both average, inferior, superior, nasal, and temporal (p value > 0.05). Mean VPD both average, inferior, superior, nasal and temporal in NAION were lower than other causes (respectively 39,98±3,69, 38,57±6,01, 36,77±5,25, 40,78±4,06, 43,91±3,42). Conclusion: This study found there is statistically significant difference between VPD among NAION and other causes in average, superior, and nasal. VPD in NAION were lower compared to other causes.